Modelling Back Pressure Power Plant to Increase Reliability and Decrease Self Power Consumption by Utilizing Residual Main Steam - Fuad, Muhammad Zainul; Afandi, Yunus; Ridho, Redho Nur (Department of Mechanical and Industrial Engineering, 2024)
The amount of steam wasted at the Kamojang PLTP in the last 4 years is quite large, having an energy potential of 7 MW (110 tons / hour) due to low unit loading dispatch, this change is not offset by the electrical energy consumption of auxiliary unit equipment so that the percentage of self-use performance (%PS) increases. In addition to the problem that office electricity loads and essential generation are still supplied by the grid (PLN) which is charged every month as an industrial customer, this results in the inability to houseload because the comporessor vent valve is supplied by grid voltage. For this reason, modeling research on the design of electricity sources was carried out that utilized the large amount of steam wasted in the Kamojang PLTP from the vent valve in the form of a back pressure type PLTP which was distributed to the 6.3 kV self-use system of the Kamojang PLTP unit. The PLTP design is modeled using cycle tempo to get power (MW) turbine generator, using Homer for financial analysis of PLTP back pressure and using ETAP to simulate the load flow of PLTP back pressure against the 6.3 kV Kamojang PLTP self-use system. Based on cycle tempo simulations and with some assumptions that the back pressure PLTP requires a steam flow of 76 tons / hour or 5 MW, and based on simulations when there is a black out of its own usage load, the Kamojang PLTP is still operating normally, which means that the unit is able to houseload and is ready to sync again faster if needed. Over the past 4 years PLTP Kamojang has lost the opportunity to reduce the %PS value by 3.34% during, and the realization of PLTP back pressure requires funds of 6,325 and will return on investment for about 1 year assuming the essential burden is fully borne throughout the year by PLTP back pressure.